Risk-Based Evacuation Model for Steel Platform Formwork in Skyscraper Construction and Its Application - HUA Ying, HE Jun, ZHAO Jincheng, ZOU Jiexin, ZHANG Jingjing, RUAN Shipeng (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
Integral steel platform formwork is widely used in the construction of super high-rise buildings, which brings a high degree of risk uncertainty to construction personnel. Therefore, it is crucial and necessary to establish a risk-based evacuation model for steel platform formwork in skyscraper construction. First, the spatial distribution of hazards sources on the steel platform is considered, hazardous areas are defined, and expert data are collected through survey questionnaires to assess the joint risk probability. Next, the joint risk probability of hazardous areas is coupled into the evacuation process based on the cellular automaton floor field model, and the evacuation process of construction personnel on the steel platform is simulated. Finally, the proposed risk-based evacuation simulation model is applied to an actual construction project. The results show that the influence of the top and lower hazardous areas on the evacuation process is significantly affected by the size of the exit. The model provides a new paradigm for experience-oriented construction safety management, with a theoretical and application value for the maintenance of the integral steel platform formwork system.